Africa in the Australian press: Does distance matter?. Issue 3 (2nd July 2016) - Obijiofor, Levi; MacKinnon, Mairead
ABSTRACT: This study examined the level of coverage given to Africa in the Australian press, including the topics that received prominence in the news, in order to understand how Africa is portrayed in Australia's press. Drawing on content analysis as a method, the research found that Africa was not portrayed in predominantly negative ways or largely misrepresented in the news, as previous studies had suggested. The result challenges the literature that suggests that Africa is depicted negatively in the Western media and that such a misrepresentation could be deliberate. The study also found that the Australian press devoted a modest amount of coverage to African news. All four regions of the continent received coverage. In general, national and local news dominated. International news came third, comprising 21 per cent of the total news articles. One lesson to be derived from this study is that events that occur in places that are geographically distant do not have to be negative to make the news, as claimed in much of the literature on foreign news.